(3JfbjM aghe Cgd GdCKQ aj Yjhf GdJhGQjN hGdSjQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3gPG cJGH PcQJ ajg ef GdJhGQjN hGdSjQ afhfG hef Ydhe GdMOjK YjhfG s
(3BNQgG (B:s
(3Je GdLRA GdChd ef JfbjM aghe Cgd GdCKQ hjJdhg ai GdLRA GdKGfi JSejI Cgd GdYbHI hcGf GdaQGZ ef JJeI gPG GdLRA SfI KdGK YTQI hKeGf eGFI s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3YdjgG Jedc heWGdYIs
(3hQO GdYfhGf HcTa GdWfhf(B: (3JdbjM aghe GdCKQI ai GdJGQjN hGdSjQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs